THE RELATIONSHIP BETWEEN MATERNAL PARENTING PATTERNS AND THE NUTRITIONAL STATUS IN TODDLERS OF FAMILIES WITH A HISTORY OF EARLY MARRIAGE IN PALU CITY: MATERNAL PARENTING PATTERNS AND THE NUTRITIONAL STATUS - Haristantia, Rifka; Khairunnisa, Khairunnisa; Azzahra, Nur Azizah; Putri, Amilah Eka (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Parenting in the family plays an important role in the growth and development of toddlers, including their nutritional status. The age of the mother at the time of marriage also affects the parenting pattern provided, including the possibility of malnutrition. This study aims to determine the relationship between maternal parenting and the nutritional status of children under five in families who marry early in Palu City. Methods: The approach in this study is quantitative. Type is an observational study, using a cross-sectional design with the free variable being the mother's parenting style, and the bound variable is the nutritional status of toddlers. This study was conducted over 2 months, from March to April 2019 with a sample consisting of 75 mothers who married early (<18 years) and had toddlers in Palu City. Data were collected through questionnaires as well as weight and height measurements with chi-square analysis and logistic regression with p<0.05. Results: The results showed that 57.3% of mothers who married early implemented good parenting, and among them, 81.4% had children with normal nutritional status. There was a significant relationship (p<0.05) between the parenting style of mothers who married early and the nutritional status of children under five in Palu City (PR=2.5; CI95% 1.21-5.20). In the multivariate analysis, there was a significant relationship between maternal education, family income, and husband support (p<0.05), while maternal work and family size with nutritional status of toddlers were not significantly linked. Mothers who marry early with good parenting are more likely to have normal nutritious toddlers than those who are not good. Conclusion: This study concludes that there is a relationship between maternal parenting and the quality of nutritional status of children under five in families who marry early.